Analysis of Nkx3.1:Cre-driven Erk5 deletion reveals a profound spinal deformity which is linked to increased osteoclast activity. Issue 1 (December 2017) - Loveridge, Carolyn; van 't Hof, Rob; Charlesworth, Gemma; King, Ayala; Tan, Ee; Rose, Lorraine; Daroszewska, Anna; Prior, Amanda; Ahmad, Imran; Welsh, Michelle; Mui, Ernest; Ford, Catriona; et al.
Abstract Extracellular signal-regulated protein kinase 5 (ERK5) has been implicated during development and carcinogenesis.Nkx3.1 -mediated Cre expression is a useful strategy to genetically manipulate the mouse prostate. While grossly normal at birth, we observed an unexpected phenotype of spinal protrusion inNkx3.1 :Cre;Erk5 fl/fl (Erk5 fl/fl ) mice by ~6–8 weeks of age. X-ray, histological and micro CT (µCT) analyses showed that 100% of male and femaleErk5 fl/fl mice had a severely deformed curved thoracic spine, with an associated loss of trabecular bone volume. Although sex-specific differences were observed, histomorphometry measurements revealed that both bone resorption and bone formation parameters were increased in maleErk5 fl/fl mice compared to wild type (WT) littermates. Osteopenia occurs where the rate of bone resorption exceeds that of bone formation, so we investigated the role of the osteoclast compartment. We found that treatment of RANKL-stimulated primary bone marrow-derived macrophage (BMDM) cultures with small molecule ERK5 pathway inhibitors increased osteoclast numbers. Furthermore, osteoclast numbers and expression of osteoclast marker genes were increased in parallel with reducedErk5 expression in cultures generated fromErk5 fl/fl mice compared to WT mice. Collectively, these results reveal a novel role forErk5 during bone maturation and homeostasisin vivo .